Analisis Evaluasi Usability Sistem Pendaftaran Online Rsu Xyz Bumiayu Menggunakan Metode Heuristics Evaluation - ito Setiawan; Melida Ratna Utami; Retno Waluyo (JURNAL REKAYASA INFORMASI, 2023)
The online registration system is a technology-based registration system where a person registers himself independently to get a service. Based on a preliminary study that was conducted with the IT team of Muhammadiyah General Hospital Siti Aminah Bumiayu, it is known that there has never been a written statement that the online registration system used has ever been evaluated related to usability since the system was first used. The purpose of this study was to find out the evaluation results of the online registration system at Muhammadiyah Siti Aminah Bumiayu General Hospital. In the evaluation process it is carried out by involving user interface experts, who have a role in helping and assessing how the system can have a good design that is in accordance with the heuristic evaluation rules. The results of this study found 47 problems from the three evaluators. If these problems are combined, the three evaluators who participated in the heuristic evaluation found 31 problem findings in total